Assessment of the potential responses of ecosystem services to anthropogenic threats in the Eten wetland, Peru - Rojas, T.V.; Bartl, K.; Abad, J.D. (Taylor and Francis Ltd., 2021)
Introduction: Coastal wetlands are currently threatened by human drivers, such as agriculture, infrastructure development, and urban sprawl. Pressures on these ecosystems disturb their morphology and biogeochemical cycles, resulting in the degradation of ecosystem services. However, little has been done to understand the wetland response to identify proper conservation strategies. Along the Peruvian coast, wetlands present a diversity of landscapes that face similar threats and pressures; however, the ecosystem response in each one may be different. Objective: This study aims to assess the environmental impacts on ecosystem services based on the understanding of geomorphic features and the status of the Eten coastal wetland (Peru). Methods: The methodology combines the application of open-source GIS tools and the collection of field data to characterize the geomorphic settings and to analyze the changes in environmental parameters. Then, the main threats and pressures on the Eten wetland are defined and related to impacts on ecosystem services using a cause-effect model. Results: Overall, the results indicated that the river plays a vital role in defining the wetland landscape and functions. The biological diversity of aquatic habitats is disturbed by hydraulic structures and agricultural activities. Current land use affects supporting and regulation services, such as water regulation.
Keywords: Wetland; Ecosystem services; Ecosystem; Threatened species; Environmental resource management; Environmental science; Urban sprawl; Habitat; Habitat destruction; Biodiversity; Land use; Agriculture; Biogeochemical cycle; Ecology; Geography; Environmental protection; https://purl.org/pe-repo/ocde/ford#1.05.08